The History of Traffic Analysis : World War I- Vietnam, 2nd Edition - Borrman, Donald; Kvetkas, William; Brown, Charles; Flatley, Michael; Hunt, Robert (Center for Cryptologic History, NSA, 2013)
The history of Traffic Analysis during World War I in Vietnam.